Development and Analysis of Synthetic Composite Materials Emulating Patient AAA Wall Material Properties. - Margossian, Christa. (2017)
Abstract: Abdominal Aortic Aneurysm (AAA) rupture accounts for 14,000 deaths a year in the United States. Since the number of ruptures has not decreased significantly in recent years despite improvements in imaging and surgical procedures, there is a need for an accurate, noninvasive technique capable of establishing rupture risk for specific patients and discriminating lesions at high risk. In this project, synthetic composite materials replicating patient-specific wall stiffness and strength were developed and their material properties evaluated. Composites utilizing various fibers were developed to give a range of stiffness from 1825.75 kPa up through 8187.64 kPa with one base material, Sylgard 170. A range of strength from 631.12 kPa to 1083 kPa with the same base material was also found. By evaluating various base materials and various reinforcing fibers, a catalogue of stiffnesses and strengths was started to allow for adaptation to specific patient properties. Three specific patient properties were well-matched with two composites fabricated: silk thread-reinforced Sylgard 170 and silk thread-reinforced Dragon Skin 20. The composites showed similar stiffnesses to the specific patients while reaching target stresses at particular strains. Not all patients were matched with composites as of yet, but recommendations for future matches are able to be determined. These composites will allow for the future evaluation of flow-induced wall stresses in models replicating patient material properties and geometries.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Robert Peattie.; Committee: David Kaplan, and Luis Dorfmann.; Keyword: Biomedical engineering.